Neuropsychological contribution to the study of white matter changes : a 10-year longitudinal study - Madureira, Sofia, 1969- (2017)
Tese de doutoramento, Ciências e Tecnologias da Saúde (Desenvolvimento Social e Humano), Universidade de Lisboa, Faculdade de Medicina, 2017